Identification and Management of Clustered Pellitory (Parietaria praetermissa) in Citrus Groves - Ramdas Kanissery; Biwek Gairhe; Brent Sellers; Steve Futch (EDIS)
In Florida, clustered pellitory is becoming a troublesome weed for citrus, especially from the winter through early summer. Inadequate management of this weed can result in its heavy infestation in tree rows and can interrupt the spray pattern of low-volume drip irrigation systems. This new 3-page publication of the UF/IFAS Horticultural Sciences Department will assist Florida citrus growers with proper identification of clustered pellitory and with adoption of adequate and timely strategies to manage this weed in their groves. Written by Ramdas Kanissery, Biwek Gairhe, Brent Sellers, and Steve Futch. https://edis.ifas.ufl.edu/hs1341